Production Performance of Broilers fed different Feed Additives - Oh, B. T.; Mak, T. K (1980)
A study of the production performance of broilers fed different feed additives (Lactozyme, Jimplex, and Nutrifac), indicated no significant difference among the treatment means concerning feed consumption and feed conversion. For weight gain, there was a significant difference (P<0.05) between the Jimplex and Control groups. Broilers from the Jimplex group were 5.92% heavier and had a higher income over feed cost per bird by $0.13 when compared to those from the con trol group at 63 days of age.